The Postliberal Order: A New Movement Emerging in American Political Thought - Wiktor Mikosza (Chrześcijaństwo-Świat-Polityka)
Some conservative American political thinkers seek a political theory that could replace contemporary liberalism. After the publishing of Patrick Deneen’s Why Liberalism Failed in 2018, a new movement in political theory emerged. Since 2021, Patrick Deneen, Adrian Vermeuele, Chad Pecknold, and Gladden Pappin started publishing together at postliberalorder.com, calling themselves The Postliberals. The paper aims at summarizing and outlining postliberal thought, along with its two main elements: Deneen’s political theory of common good conservativism and Vermeuele’s legal theory of common good constitutionalism, asking the question of whether postliberalism, as represented by the authors, is a new political doctrine or rather an emerging intellectual movement.